LAPORAN KASUS SKIZOFRENIA PARANOID - Adhayani Lubis (PRIMER (Prima Medical Journal), 2023)
Schizophrenia is a clinical syndrome of various psychopathologies involving cognition, emotion, perception, and other aspects of behavior. Schizophrenia is defined and diagnosed as a psychiatric disorder solely based on its clinical phenomenology. In this case, a 37-year-old man came with the main complaint of hearing disturbing whispers in his ear and believing that his family always talked about him. The patient is also suspicious of his parents and siblings, irritable, often alone, and unable to sleep. The patient also had auditory hallucinations, visions, and prominent delusions. The therapy given to patients was risperidone 2 x 1 mg orally / day and education for patients and their families. The patient's condition improved by showing a cooperative attitude that felt much calmer, and the patient never suspected his family and siblings again. Auditory hallucinations that appear can be controlled.